ANALISIS KEBUTUHAN MODEL PBL BERBASIS VIDEO BONEKA INTERAKTIF PADA MATERI ZAKAT DI SEKOLAH DASAR - Eprilia, Winda; Raharjo, Makmum; Nurhasan, Nurhasan (Dharmas Education Journal (DE_Journal), 2023)
This research was conducted due to the importance of knowladge about zakah material as one of the pillars of islam however many students did not understand it. In addition learning based on PBL model had its own urgency in supporting the establishment of a quality generation that has 21st century skills. The aim of this research was to know the students' needs for PBL model based on the interactive doll video media on zakah material in elementary schools. Qualitative method was implemented in this research and  the questionnaire data analysis was carried out quantitatively with the reserach subjects of students and teachers in sixth grade. The results of this research on the needs of 22 students showed that 68.18% of students had difficulty in learning zakah material, 77,27% students were not interested in learning with conventional method and 95,45% enjoy learning process using media. However based on the infirmation from the teacher, the used of learning media was still  rarely done. 100% students were agree if there was PBL model based on the interactive doll video media on islamic religion subject especially in zakah material. This was also supported by religion teacher that must be followed the development of the times in the 21st century era. These results indicate the need to develop interactive doll video learning media integrated with the PBL model. Visualization through interactive doll videos was expected to help illustrate zakah concepts.this research was also to encourage the development of more innovative learning materials that incorporate technology and PBL approaches for various subjects in primary schools.